Flameless Combustion in Toroidal Combustion Chamber for Reduced Nitrogen Oxides (NOX) Formation - Ong, Seong Shin (2016)
Flameless combustion is a unique combustion process, which produces no visible flame, low noise and an overall temperature throughout the process which is lower compared to conventional combustion processes. Flameless combustion can be achieved through large amounts of exhaust gas recirculation. However, the allowance frame of the amount of recirculation is very narrow, where too much of exhaust gas recirculation will immediately stop the combustion process. Flameless combustion is a promising combustion technology available today to suppress emission of pollutants such as nitrogen oxides, and in suppressing the thermal NO formation through the combustion process. Nitrogen oxides (NOx) are among the hazardous polluting gases released from the combustion process. Flameless combustion is a unique combustion process, which produces no visible flame, low noise and an overall temperature throughout the process which is lower compared to conventional combustion processes. Flameless combustion can be achieved through large amounts of exhaust gas recirculation. However, the allowance frame of the amount of recirculation is very narrow, where too much of exhaust gas recirculation will immediately stop the combustion process. Flameless combustion is a promising combustion technology available today to suppress emission of pollutants such as nitrogen oxides, and in suppressing the thermal NO formation through the combustion process. Nitrogen oxides (NOx) are among the hazardous polluting gases released from the combustion process.